Inti Games : launch Helix in Australia or wait? - Cai, Jiayu; Dang, Chenyuan; Tan, Alvin; Hulsink, Willem (London : SAGE Publications Ltd, 2017)
Helix is Inti Game, a Rotterdam-based start-up's innovative outdoor sports product. After successfully selling Helix on the Dutch home market, Inti Games planned to expand internationally, with Australia being its first market to enter and with the U.S. and U.K. in the pipeline. They had signed a major contract with an Australian distributor who was keen to introduce Helix there. A successful sale in Australia would lay the foundation for future moves into the other key English-speaking markets. However, problematic productions in China derailed the plan. As the scheduled product launch date was approaching, the products at Chinese factories were only 80% complete, and their quality was not yet established by test runs. The two founders of Inti Games - De Schipper and Van Rijn - did not wish to lose the Australian market to competitors by delaying product delivery, nor did they wish to damage Helix's or Inti Game's reputation by introducing defective products to the market. They had to make a quick decision regarding whether to launch Helix in Australia or wait until the following year.
Originally Published InCai, J., Dang, C., Tan, A., & Hulsink, W. (2014). Inti Games: Launch Helix in Australia or wait? Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Inti Games -- Case studies; Business logistics -- Case studies; Total quality management -- Case studies